Effect of direct oral feeding following minimally invasive esophagectomy on costs and quality of life. (1st January 2021) - Pattamatta, Madhuri; Fransen, Laura F. C.; Dolmans-Zwartjes, Annemarie C. P.; Nieuwenhuijzen, Grard A. P.; Evers, Silvia M. A. A.; Kouwenhoven, Ewout A.; van Det, Marc J.; Hiligsmann, Mickael; Luyer, Misha D. P.
Abstract: Aims: Following (minimally invasive) esophagectomy, patients often rely on tube feeding, since oral intake is often delayed. Consequently, additional support by a dietician and home care is needed until oral intake is commenced. In this study, the effects of direct start of oral feeding compared with tube feeding following an esophagectomy was evaluated on treatment costs and health-related quality of life (QoL). Methods: Patients undergoing a minimally invasive esophagectomy were randomized in the NUTRIENT II study between controls (nil-per-mouth during 5 days and subsequent tube feeding) and a group in whom oral feeding was started directly postoperatively. Total hospital costs (including readmission and outpatient costs) and home care data for a period of 6 months after surgery were analyzed. QoL (measured using EORTC-QLQ-C30 and EORTC OG-25) was assessed preoperatively and 6 weeks, 12 weeks, and 6 months postoperatively. Results: A total 132 patients were included ( n  = 65 direct oral feeding group and n  = 67 control group). Mean patient hospital costs were €26, 014 in the intervention group over a 6-month period compared to €26, 989 in the control group ( p  = .825). Furthermore, people with direct oral feeding required significantly less home care assistance; i.e. 23 (48.9%) intervention patients versus 37 (77.1%) control patients ( p  = .004). Also, QoL in patients with direct oral feeding progressed more quickly when compared to the control group. Limitations: Hospital costs were derived from a single hospital unit whereas costs from all the participating units may be a better reflection of the cost deviation. Availability of homecare data was limited, leading to difficulty in detecting differences in costs. Conclusion: This study suggests that direct oral feeding leads to similar total costs and a significantly reduced need for home care assistance. Furthermore, QoL in intervention group increased more quickly when compared to the control group.